Humiliation as a Consequence of Human Offenses (A Study of the Interpretation of the Verses of Azabulkhizyi from the Perspective of Tafsir al-Maraghi) - Farhan Gafinda, Muhammad; Sulthoni, Akhmad; Saputra, Akhmadiyah (JIA (Jurnal Ilmu Agama), 2024)
Every human being has consequences for what they have done. Especially because of their lack of faith and trust in themselves. Allah has warned his servants about the consequences of doing things that Allah has forbidden. One of them is punishment. Although there have been several essays on doom, the author tries to convey how to avoid doom. The word doom means God's punishment that is rewarded to humans who violate religious prohibitions. doom also means all kinds of suffering (misery). There are many assumptions about the cruelty of God about the punishment given but not realizing the mistakes that have been made. This study examines the interpretation of the word doom in Tafsir al-Maraghi by Sheikh Ahmad Mustafa al-Maraghi. This study focuses on two main things: first, the interpretation of Shaykh Ahmad Mustafa al-Maraghi on the verses related to punishment. Second, how efforts to avoid doom in Tafsir al-Maraghi. The research method used is library research with a thematic approach using the Qur'an and Tafsir al-Maraghi as the main source. The results and conclusions show that al-Maraghi's interpretation of the verses of azabulkhizyi is interpreted as an act that causes Allah's punishment to befall humans. These actions include disobeying and fighting Allah and His Messenger, showing hypocrisy, spreading false teachings, and doing vain deeds. This finding indicates that azabulkhizyi tells how the consequences of human beings about what they have violated from Allah's provisions.